Climate change influences foliar nutrition and metabolism of red maple (Acer rubrum) trees in a northern hardwood forest. Issue 2 (21st February 2022) - Blagden, Megan; Harrison, Jamie L.; Minocha, Rakesh; Sanders‐DeMott, Rebecca; Long, Stephanie; Templer, Pamela H.
Abstract: Mean annual air temperatures are projected to increase, while the winter snowpack is expected to shrink in depth and duration for many mid‐ and high‐latitude temperate forest ecosystems over the next several decades. Together, these changes will lead to warmer growing season soil temperatures and an increased frequency of soil freeze–thaw cycles (FTCs) in winter. We took advantage of the Climate Change Across Seasons Experiment (CCASE) at the Hubbard Brook Experimental Forest in the White Mountains of New Hampshire, USA, to determine how these changes in soil temperature affect foliar nitrogen (N) and carbon metabolism of red maple ( Acer rubrum ) trees in 2015 and 2017. Earlier work from this study revealed a similar increase in foliar N concentrations with growing season soil warming, with or without the occurrence of soil FTCs in winter. However, these changes in soil warming could differentially affect the availability of cellular nutrients, concentrations of primary and secondary metabolites, and the rates of photosynthesis that are all responsive to climate change. We found that foliar concentrations of phosphorus (P), potassium (K), N, spermine (a polyamine), amino acids (alanine, histidine, and phenylalanine), chlorophyll, carotenoids, sucrose, and rates of photosynthesis increased with growing season soil warming. Despite similar concentrations of foliar N with soil warming with and without soil FTCs in winter, winter soil FTCs affected other foliar metabolic responses. The combination of growing season soil warming and winter soil FTCs led to increased concentrations of two polyamines (putrescine and spermine) and amino acids (alanine, proline, aspartic acid, γ‐aminobutyric acid, valine, leucine, and isoleucine). Treatment‐specific metabolic changes indicated that while responses to growing season warming were more connected to their role as growth modulators, soil warming + FTC treatment‐related effects revealed their dual role in growth and stress tolerance. Together, the results of this study demonstrate that growing season soil warming has multiple positive effects on foliar N and cellular metabolism in trees and that some of these foliar responses are further modified by the addition of stress from winter soil FTCs.